Fraud - A multidisciplinary element. Famous case studies in such different fields - Chiriac (Matei), Alina; Nișulescu, Ileana; Aivaz, Kamer-Ainur (Technium Social Sciences Journal, 2021)
Research Question: RQ1: What is fraud? RQ2: Where do we find fraud? It is fraud a multidisciplinary element? Why? Motivation: Most of the literature states that fraud is a topic of great interest, but no one has tried to prove why, but also to show how much interest in publishing about the subject of fraud has increased. Idea: Our study looked at an international database (Web of Science) to demonstrate the growing interest in studying fraud in various fields. But we also did a case study presenting a complex case of fraud, discovered by DGAF in Romania. Data: The data were collected from Web of Science database and an analysis was made based on the 17,825 results found when searching for the word "fraud", and then we also did a case study presenting a complex case of fraud, discovered by DGAF in Romania, collecting data by direct observation of one of the authors. Tools: To test study’s hypotheses, we analyzed the Web of Science database. Findings: The results answer in the affirmative to the research question. Also, the implications of the results are that all actors can outline an overview of the phenomenon, but especially reveals the gaps in the discovery of the phenomenon. Contribution: Most of the literature states that fraud is a topic of great interest, but no one has tried to prove why, but also to show how much interest in publishing about the subject of fraud has increased.